Assessing contraceptive knowledge and usage among currently married women in Mizoram - Pautunthang, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Limited research on the issue of contraception in Mizoram prompted this study to assess contraceptive knowledge and usage among currently married women aged 15-49 using data from the national family health survey (NFHS). Methods: Univariate and bivariate analysis was performed using SPSS-25 to analyse the NFHS data from Mizoram, focussing on the levels and trends in contraceptive knowledge and usage among currently married women aged 15-49 in Mizoram with selected background characteristics. Results: Findings reveal a notable disparity between contraceptive knowledge (99.5%) and its actual usage (31.2%) among currently married women aged 15-49 in Mizoram. The contraceptive usage among currently married women aged 15-49 has declined from 59.9 per cent in 2005-06 to 31.2 per cent in 2019-21. Modern contraceptive methods are preferred over traditional ones, with female sterilisation being the most common method. Male sterilisation (vasectomy) is almost non-existent. District-level disparities exist, with the Aizawl district at 21.6 per cent and the Champhai district at 50 per cent contraceptive usage, according to NFHS-5 (2019-21). Factors influencing contraceptive usage include place of residence, educational level, and number of children. Unmet needs for contraception decreased between 2015-16 and 2019-21. Conclusions: The study highlights the urgent need for interventions to bridge the gap between contraceptive knowledge and usage among currently married women aged 15-49 in Mizoram. Efforts should focus on promoting modern contraceptive methods addressing district-level disparities. Additionally, initiatives to reduce unmet needs, particularly for spacing methods, are crucial for improving contraceptive usage among currently married women aged 15-49 in Mizoram.